(untitled) ([Ha Noi], 2005)
This document is part of a broader capitalization and extension program developing the lessons learned from the DIALOGS project, which includes: a series of 15 summary sheets for operators in the field ; a summary document comprising the series of posters displayed at provincial seminars ; and a comprehensive capitalization document converting the lessons learned from the project.
Keywords: Bảo vệ người tiêu dùng,Consumer protection,Kinh tế nông nghiệp,Agriculture,Rural development,Genetically modified foods; International cooperation,Government policy; Vietnam,Việt Nam,Vietnam,Vietnam